UPAYA PENINGKATAN KETERAMPILAN MENULIS EKSPOSISI MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SDN 99 KAMPUNG BERU KECAMATAN GALESONG KABUPATEN TAKALAR - Andi Nurul Elvira Ningsih; Abd Rahman Rahim; M. Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main issue in this study is how to improve expository writing skills through the Problem- Based Learning (PBL) model in grade V at SDN 99 Kampung Beru, Galesong District, Takalar Regency. This study aims to describe the results of improving students' expository writing skills through the Problem-Based Learning (PBL) model in grade V at SDN 99 Kampung Beru, Galesong District, Takalar Regency. This research is a classroom action research (CAR) conducted at SDN 99 Kampung Beru. The research was carried out in two cycles, with each cycle consisting of three meetings. The data collection instruments in this research were test sheets containing essay questions administered at the end of each cycle meeting and observation sheets. Based on the research results, in Cycle I, it was found that students with incomplete scores had an average score of 54.54 in the low category, with 6 students. There were also 5 students who achieved completion with an average score of 45.45 in the high category. In Cycle II, the success of the intervention had improved. There were 5 students with an average of 45.45 in the very high category and 5 students with an average of 45.45 in the high category. Based on the above results, it can be concluded that 10 students achieved passing grades. One student did not achieve a passing grade, with an average score of 9.1.